Immunoadsorption in neurological disorders. Issue 5 (October 2017) - Oji, Satoru; Nomura, Kyoichi
Abstract: In recent years, immunoadsorption has been increasingly recognized as an alternative to therapeutic plasma exchange and used for the treatment of neurological disorders such as Guillain–Barré syndrome, chronic inflammatory demyelinating polyneuropathy, myasthenia gravis, neuromyelitis optica spectrum disorders, and multiple sclerosis, as well as autoimmune encephalitis. Unlike therapeutic plasma exchange, which requires fluid replacement with a blood solution such as fresh frozen plasma or albumin, immunoadsorption is a blood purification technique that enables the selective removal of humoral factors from separated plasma through a high-affinity adsorbent with tryptophan or phenylalanine. Although the mechanisms underlying the therapeutic effects of immunoadsorption treatment remain to be fully elucidated, they are based on the removal of pathogenic humoral factors from circulating blood, such as disease-specific autoantibodies, complement, and inflammatory cytokines. The American Society for Apheresis has published evidence-based guidelines on the use of therapeutic apheresis in clinical practice, with specific instructions on 16 neurological disorders. However, the modality recommended in the guidelines for most of these disorders is therapeutic plasma exchange. This part of our review focuses on the clinical aspects of immunoadsorption. We also describe the efficacy of immunoadsorption and the evidence obtained by previous studies of the treatment of neurological disorders. Immunoadsorption could greatly improve the treatment of patients with autoimmune neurological disorders but further evidence is needed to confirm the efficacy of immunoadsorption in clinical practice.